Regional dimension of implementing humanitarian initiatives within the community with a shared future for mankind: China’s cooperation with African states - Bingjun, Ma (Journal of the Belarusian State University. International Relations, 2025)
This article elucidates Africa’s considerable role in shaping a community with a shared future for mankind. It analyses the core elements and practical implications of the recent initiative «Jointly building an all-weather China – Africa community with a shared future in the new era» announced by Xi Jinping at the 2024 Forum on China – Africa cooperation. This is a landmark initiative, representing a significant diplomatic achievement for African nations. The study contends that China’s humanitarian assistance and its broad engagement with Africa in areas such as culture, education, healthcare, and infrastructure are anchored in the idea of a shared future, ensuring equitable partnership and reciprocal advantage. The analysis further demonstrates that the South Africa, amidst intensified China – Africa collaboration, serves as an effective intermediary between China and the wider continent. Through bilateral and multilateral engagement, notably within BRICS and international organisations, the South Africa actively advances the goal of a shared future for mankind.